Effects of Leadership Development Programs, Mentorship, and Employee Empowerment on Organizational Performance - Soegiarto, Ita; Rahmadhani, May Vitha; Ainul Arifah, Nur Jihan; Ilham, Ilham (International Journal of Business, Law, and Education, 2024)
This study investigates the effects of Leadership Development Programs, Mentorship, and E mployee Empowerment on organizational performance in Indonesian companies. Using a sample of 2000 respondents and employing SPSS for data analysis, the study finds that all three factors significantly and positively impact organizational performance. The regression analysis reveals that Leadership Development Programs (Beta = 0.322, p = 0.005), Mentorship (Beta = 0.298, p = 0.000), and Employee Empowerment (Beta = 0.384, p = 0.000) are strong predictors of organizational performance. The overall model explains 67.4% of the variance in organizational performance (R² = 0.674). Additionally, normality and multicollinearity assessments confirm the robustness of the model. These findings underscore the critical role of leadership development, mentorship, and employee empowerment in enhancing organizational outcomes. The study provides valuable theoretical contributions and practical implications for organizational leaders aiming to improve performance through strategic investments in these areas.